Analisis tebal lapis tambah perkerasan lentur (overlay) menggunakan metode manual desain perkerasan jalan 2017 Jalan Gandusari – Kampak Kabupaten Trenggalek (Sta 12+000–15+000) - Indra Hardiansyah; Nurani Hartatik; Satiya Wardhana; I Gede Agus Punarta (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2024)
Gandusari - Kampak Road is a class II collector road and 2/2 TT Road Type with a length of 17 km located in Trenggalek Regency, the road is often used by the community to support the economy, tourism, politics, education and others. The large number of motorized vehicle activities has resulted in a decrease in service and quality on the road. The damage to the road disrupts traffic and road users, can be seen visually structural damage, such as surface defects, cracks and release of aggregate grains, so that an overlay is needed to increase structural value and prevent further damage. In this study, the 2017 Road Pavement Design Manual method was used to determine the thickness of the overlay by utilizing empirical data from deflection tests and condition analysis and integrating structural analysis based on traffic loads. This method is a technical guideline issued by the Ministry of PUPR. In the analysis of the thickness of the overlay, deflection data and traffic loads were used as determining variables for the thickness of the overlay. In this study, secondary data was used in the form of Benkelman Beam (BB) deflection and average daily traffic data obtained from the PUPR Office of Trenggalek Regency. Based on the analysis results, the CESA4 value is 4,281,450.00 ESA and CESA5 is 6,950,077.00 ESA. It can be concluded that the thickness of the overlay obtained during the 10-year design life based on the maximum deflection D0 of 0.419 mm produces an overlay thickness of 6 cm. If reviewed based on the deflection curve D200 of 0.248 mm, it produces an overlay thickness of 10 cm. From the results of traffic analysis and prevention of fatigue cracks before the design life, an overlay thickness of 10 cm was taken. This aims to increase the capacity of the structural performance and service life of the old pavement, so that the Gandusari - Kampak road can function safely and comfortably for users. This study focuses on sta 12 + 000 - sta 15 + 000 with an overlay of 10 cm.